Comparison of Satisfaction Between Menstrual Pad-Based HPV Self-Collection and Clinician-Collected HPV DNA Testing in Thai Women - suvansanya,MD, Piyapong; Sitipredanant, Piyamart; Sadangrit, Kawalee (The Bangkok Medical Journal, 2025)
OBJECTIVES: Cervical cancer remains a significant public health concern in Thailand, where participation in screening programs is limited due to psychological, cultural, and logistical barriers. Menstrual pad-based HPV self-collection (Q-pad) presents a non-invasive, private, and potentially acceptable alternative to clinician-collected HPV testing. This study aimed to compare the acceptability of Q-pad self-collection with clinician-collected thin-layer liquid-based HPV DNA testing, and to explore factors influencing women’s screening preferences. MATERIALS AND METHODS: A cross-sectional study was conducted among 158 Thai women aged ≥35 years undergoing annual health check-ups. Each participant underwent both clinician-collected HPV DNA testing and Q-pad self-collection at home. Satisfaction levels were assessed using a five-point Likert scale, and qualitative feedback was collected through open-ended responses. Descriptive analysis was performed to compare satisfaction levels and identify key themes related to user preferences and barriers. RESULTS: Most participants (83.5%) reported equal satisfaction for both methods. For the Q-pad test, 91.8% of participants rated the experience as “very good” or “excellent,” while 98.1% did so for the clinician-collected test. A minority expressed a preference, with 13.3% favouring clinician collection due to perceived accuracy and 3.2% preferring self-collection for its privacy and comfort. Both screening methods received high levels of satisfaction. For the Q-pad test, 91.8% of participants rated the experience as “very good” or “excellent,” while 98.1% did so for the clinician-collected test. CONCLUSION: Q-pad self-collection demonstrated high levels of participant satisfaction, nearly comparable to clinician-collected HPV testing. These findings suggest that Q-pad self-collection is an acceptable alternative screening approach that could complement existing clinician-based programs